Modelagem na/da Educação do Campo e suas relações com a Educação Popular de Paulo Freire - Leite, Kátia da Costa; Silveira, Everaldo; Magnus, Maria Carolina Machado (Revista de Educação Popular, 2024)
This work presents and deepens some discussions carried out in the context of doctoral research that deals with the articulation between Mathematical Modeling and Countryside Education. In this way, we seek to highlight some intertwinings between Countryside Education and Mathematical Modeling with the ideals of the Popular Education perspective proposed by Paulo Freire that were noticed during the investigative process. To carry out the research, we analyzed one thesis, ten dissertations and 24 articles that deal with the articulation of Mathematical Modeling with Rural Education, published between 2008 and 2023 in Brazil. The analysis of the material allows us to demonstrate that, based on the relationships/approximations found between these two perspectives, we recognize that freirean assumptions are at the basis of the connection between Modeling and Countryside Education and, therefore, we realize Modeling in/of Countryside Education as a potential for teaching and learning in countryside schools. We were able to conclude that the proposal for a Mathematical Modeling in Countryside Education takes into account the educational project of the Movement for Countryside Education (its pedagogical principles and the specificities of peasant territories). Furthermore, Modeling activities need to be combined with the concept of Critical Mathematics Education, proposed by Ole Skovsmose (2001; 2007; 2008; 2014), and be conceived in the socio-critical perspective of Modeling, which foresees teaching for transformation and social justice.